Comparative performance of different regional native sheep in Bangladesh (Bangladesh Veterinarian, 2012)
This study was undertaken to investigate the performance of native sheep in Bangladesh. Data were collected during 2004-2010 from sheep of the Barind, Jamuna and Coastal areas. The phenotypic characteristics did not differ significantly, but ears were shorter in Barind than in Jamuna and Coastal sheep. The coat colour was 45% white, 26% brown, 24% white brown and 3% black brown in Barind and Jamuna sheep, but white (70%) and white brown (30%) in Coastal sheep. Differences were not significant for age at first heat, age at first pregnancy and age at first lambing. Days open and post-partum ewe weight were significantly (P